ANALISIS AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN DANA DESA NGRASEH - Alan Nuril Khoir; Febry Fabian Susanto (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2025)
This study aims to analyze the implementation of accountability and transparency in the management of Village Funds through the perceptions of Ngraseh Village officials. The primary concern is the limited disclosure of village financial reports to residents, despite the village's compliance with applicable regulations. This study uses a qualitative descriptive method. Data was obtained through in-depth interviews, observations, and documentation. The results of the study show that the implementation of accountability in Ngraseh Village has been running well through the use of the Siskeudes application, which ensures that every financial transaction is recorded in an orderly, accurate, and documented manner in accordance with local government regulations. Based on these research results, the implementation of transparency within the community has been quite effective, achieved through various media, including direct information boards and activities. However, financial reports are not published to the villagers. It can be concluded that the management of Village Funds in Ngraseh Village has fulfilled the aspect of vertical accountability to the local government; however, it still needs to be strengthened in terms of transparency to the villagers. Therefore, increased publication and public participation are necessary to realize full good governance principles.